2021
DOI: 10.3389/fonc.2020.582504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antiviral Therapy on HBV Reactivation and Survival in Hepatocellular Carcinoma Patients Undergoing Hepatic Artery Infusion Chemotherapy

Abstract: BackgroundThis study aimed to investigate the influence of hepatic artery infusion chemotherapy (HAIC) on hepatitis B virus (HBV) reactivation in hepatitis B surface antigen (HBsAg) positive patients with primary hepatocellular carcinoma (HCC) as well as evaluate the role of antiviral prophylaxis in these patients.MethodsWe enrolled 170 HBsAg-positive advanced HCC patients receiving HAIC using mFOLFOX regimen, of which 137 patients received antiviral prophylaxis. Risk factors for HBV reactivation were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…It has been reported that HBV reactivation had no significant association with OS in HCC receiving HAIC with antiviral treatments. 28 Nucleoside analogs can inhibit hepatitis activity and reverse liver function, which improves patients’ tolerance to anticancer therapy and survival. 29 Second, HBV loads were only measured at baseline, while the changes in viral loads were not regularly monitored.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It has been reported that HBV reactivation had no significant association with OS in HCC receiving HAIC with antiviral treatments. 28 Nucleoside analogs can inhibit hepatitis activity and reverse liver function, which improves patients’ tolerance to anticancer therapy and survival. 29 Second, HBV loads were only measured at baseline, while the changes in viral loads were not regularly monitored.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…HBV reactivation was defined as an increase of serum HBV DNA > 1 log or reappearance of HBV DNA in patients with undetectable HBV DNA at baseline in 33 studies, [ 19–21,23–30,32–36,38–43,45–48,50–53,56–58 ] while this definition varied in five studies [ 31,44,49,55,59 ] and was not clearly provided in the remaining three studies. [ 22,37,54 ] A definition of HBV‐related biochemical reactivation was not provided in 18 studies, [ 21–27,30,32–34,37–41,54,59 ] while it varied widely among the remaining 23 studies.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19,40,42 ] Biochemical reactivation was reported in 144 (10.6%) of 1354 patients from eight studies (pooled estimate, 11%; 95% CI, 6%–20%; heterogeneity, p < 0.01) (Figure 4D). [ 19,20,35–37,42,43,58 ] Biochemical reactivation was diagnosed in only 4/173 (2.3%) patients included in two studies who received prophylactic NA and in 15/70 (21.4%) patients included in the same studies who did not. [ 35,43 ] Eight studies reported biochemical reactivation rates in a total of 795 patients receiving no prophylactic NA (pooled estimate, 16%; 95% CI, 10%–25%; heterogeneity, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations